Better tolerability of St. John's wort extract WS 5570 compared to treatment with SSRIs: a reanalysis of data from controlled clinical trials in acute major depression - Kasper, Siegfried; Gastpar, Markus; Möller, Hans-Juergen; Müller, Walter E.; Volz, Hans-Peter; Dienel, Angelika; Kieser, Meinhard (International clinical psychopharmacology, 2010)
Selective serotonin reuptake inhibitors (SSRIs) like paroxetine have replaced older antidepressants mainly because of a more favorable safety profile, but they are still associated with burdensome side effects. We investigate the tolerability of St. John's wort extract WS 5570, a herbal antidepressant with proven efficacy, in comparison to paroxetine and other SSRIs and placebo.
Gesehen am 07.03.2023